Diatomáceas na bioindicação de mudanças paleoambientais em planície de inundação - Ruwer, Daiane Trevisan (2020)
The paleolimnological approach one of the few existing methods that assesses the rate of ecosystem changes in freshwater environments, over large time scales, and one of the few approaches that have been used successfully to infer pre-impact limnological conditions and post-perturbation trajectories of environmental changes. The diatoms are the most effective bioindicator microfossils in paleolimnological research in providing information on environmental changes in aquatic ecosystems. Among the ecosystems that have been altered over time, the floodplain of the Upper Paraná River in recent decades has been subjected to several natural and man-made disturbances, mainly hydroelectric dams, which have affected the entire ecosystem and the known freshwater biodiversity. Therefore, the temporal pattern of abundance and functional traits of the diatoms community of two lakes inserted in this floodplain was investigated, using the paleolimnological approach to infer a history of possible environmental changes. The results of these studies were divided into three works. Through the bioindication of the most abundant diatom species in Garças Lake and Patos Lake, it was possible to observe evidence of physical, chemical and hydrological changes in both environments over the last 100 years. It is inferred that both environments may have been influenced by effects imposed by the upstream reservoirs and climatic events. As well as the greater variation and reduction in functional diversity found in Garças Lake, which is closer to dams, indicates a greater influence of the reservoirs. Despite this, in different periods, both lakes have replaced and simplified similar functional categories, which are related to low water conditions and high turbulence in the water column, which were recurrent after the damming periods.